Design and numerical analysis of a modified core hexa–deca photonic crystal fiber for highly negative dispersion and birefringence control in optical communication bands - Amit Halder; Md. Shamim Anower (Scientific Reports)
Abstract The paper presents a thorough investigation into the design of a Modified Core Hexa–Deca Photonic Crystal Fiber (MHD-PCF) with adjustable features to regulate dispersion and birefringence. At the target wavelength of 1550 nm, the suggested MHD-PCF exhibits extraordinary optical properties, including an ultra-high negative dispersion coefficient of − 7755 ps/(nm km) and significant birefringence of 1.905 × 10−2. The analysis entails regular changes in lattice constants and center air hole parameters, which provide insights into optical property trends. The MHD-PCF regularly exceeds existing benchmarks across a wide range of parameter adjustments. Notably, this fiber has strong nonlinearity (59.12 W−1 km−1) and low confinement loss (2.896 × 10−3 dB/cm), as well as an enhanced numerical aperture (0.5144), demonstrating its potential for efficient light coupling and supercontinuum production. These results put the Modified Core Hexa–Deca Photonic Crystal Fiber at the forefront of contemporary communication systems, and its optical enhancements and flexible features present exciting opportunities for novel Terahertz technology breakthroughs, especially in the areas of communication systems and sensing applications.